Perbandingan Pengukuran Cardiac Output, Cardiac Index, dan Systemic Vascular Resistance Antara Menggunakan Non-Invasive Cardiometry (Icon®) dan Pressure-Recording Analytic Method (MOST- CARE®) pada Pasien Pascaoperasi Mayor di RSUP Dr. Sardjito Yogyakarta - Daniswara; Wisudarti, Calcarina Fitriani Retno; Kurniawaty, Juni (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Background: Pulmonary Artery Catheter (PAC) is the gold standard for examining cardiac output (CO), cardiac index (CI), and systemic vascular resistance (SVR), however, PAC insertion is very invasive, causing complications. A less invasive method is currently being developed in the form of Most-Care® (pressure recording analytical method (PRAM)) and non-invasive ICON® (electrical cardiometry (EC)). Methods: The study sample was adult patients who were treated in the ICU Dr. Sardjito with age ≥ 18 years,post major surgery with an arterial line and central venous catheter (CVC). CO, CI, and SVR values were measured at the first hour after the patient arrived at the ICU using ICON® and Most-Care®. Collected data were processed and analyzed to compare between two of them using paired ttest. Results: From a total population of 49 patients, 23 subjects met the inclusion criteria, and the remaining 26 subjects were eliminated due to CHF, obesity, atrial fibrillation, tachycardia, bradycardia, and thoracic surgery. CO and CI of ICON® and Most-Care® are not significantly different (p>0.05). High SVR of ICON® and Most-Care® are not significantly different (p=0.667), but showed a significant difference in normal SVRp=0.015. Conclusion: The measurement of CO and CI between ICON® and Most-Care® showed no significant difference (p>0.05), but showed a significant difference (p=0.015) in the normal SVR category